Antioxidant, antimicrobial, enzyme inhibitory and cytotoxic effect of Taverniera couneifolia plant mediated Silver nanoparticles - Khan, Rahmat; Muhammad Nisar Ul Haq; Ghulam Mujtaba Shah; Wahid Ullah; Khursheed Ur Rahman; Zamarud Shah; Ammara Khan; Feroz Khan; Matiullah; Ihsan Ullah; Hajra Afeera Hamid; Hajra Afeera Hamid (LIAQUAT MEDICAL RESEARCH JOURNAL, 2024)
This study was conducted to evaluate antioxidant, anticancer, enzyme inhibitory and antimicrobial potential of methanolic extract and AgNPs of T. couneifolia. The (DPPH) 1,1-diphenyl-2-picrylhydrazyl, (ABTS) 2,2-azinobis-(3-ethylbenzothiazoline-6-sulfonic acid), metal chelating, phosphomolybdenum, hydrogen peroxide scavenging and (FRAP) ferric reducing antioxidant power activities, antibacterial potential against Klebsiella pneumonia, Escretia coli, Acetobacter, Staphylococcus aureus and Staphylococcus epidermidis, antifungal against Aspergillus niger and Aspergillus flavus and enzyme inhibitory including alpha amylase and acetyl cholinesterase were used to evaluate the methanolic extract and the synthesized AgNPs' antioxidant potential. T AgNPs displayed the highest enzyme and radical scavenging capabilities in comparison to the plant extract. Additionally, the BSL test was used to measure the cytotoxicity activity. Our findings unequivocally demonstrated that biosynthesized AgNPs had antimicrobial, antioxidant, enzyme inhibitory and cytotoxic action and reduced the growth capability.